1994
DOI: 10.3758/bf03211678
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric contributions to the integration of visual and auditory information in speech perception

Abstract: Differential hemispheric contributions to the perceptual phenomenon known as the McGurk effect were examined in normal subjects, 1 callosotomy patient, and 4 patients with intractable epilepsy. Twenty-five right-handed subjects were more likely to demonstrate an influence of a mouthed word on identification of a dubbed acoustic word when the speaker's face was lateralized to the LVF as compared with the RVF. In contrast, display of printed response alternatives in the RVF elicited a greater percentage of McGur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
3
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 31 publications
(34 reference statements)
2
29
3
1
Order By: Relevance
“…Although both left-field (R. Campbell, 1986) and right-field (R. Campbell, de Gelder, & de Haan, 1996) advantages have been observed for static face tasks, a right visual field advantage was reported for silent speechreading (Smeele, Massaro, Cohen, & Sittig, 1998). Two other studies (Baynes, Funnell, & Fowler, 1994;Diesch, 1995) also showed a right visual field advantage for the audiovisual fusion effect provided by incongruent McGurk stimuli such as ours. Most of these studies used small gaze displacements (,5º from central fixation) and did not directly manipulate stimulus eccentricities, with the exception of Smeele and colleagues (Smeele et al, 1998), who reported a reliable decrease in speechreading performance when the subject's gaze was displaced eccentrically (but within 10º) from the talking face.…”
Section: Resultsmentioning
confidence: 41%
“…Although both left-field (R. Campbell, 1986) and right-field (R. Campbell, de Gelder, & de Haan, 1996) advantages have been observed for static face tasks, a right visual field advantage was reported for silent speechreading (Smeele, Massaro, Cohen, & Sittig, 1998). Two other studies (Baynes, Funnell, & Fowler, 1994;Diesch, 1995) also showed a right visual field advantage for the audiovisual fusion effect provided by incongruent McGurk stimuli such as ours. Most of these studies used small gaze displacements (,5º from central fixation) and did not directly manipulate stimulus eccentricities, with the exception of Smeele and colleagues (Smeele et al, 1998), who reported a reliable decrease in speechreading performance when the subject's gaze was displaced eccentrically (but within 10º) from the talking face.…”
Section: Resultsmentioning
confidence: 41%
“…A number of functional neuroimaging studies have shown that females engage the right perisylvian cortex more than do males for phonologically based language tasks (Jaeger et al, 1998;Pugh, Shaywitz, Shaywitz, Constable, et al, 1996;Rossell et al, 2002;Shaywitz et al, 1995). In addition, previous research has indicated that there is a right-hemisphere (RH) processing advantage for audiovisually presented speech (Baynes, Funnell, & Fowler, 1994;Diesch, 1995). Bilaterality in female perceivers' neural organization has been proposed to lead to faster or more efficient processing of incongruent auditory and visual speech (Coney, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier study [3], tachistoscopic displays of low illumination and low contrast were used; more different mouth shapes all produced by a single speaker--were seen. In Baynes et al's study [1], moving facial stimuli were seen on a video display. All these conditions may foster a reduced RVF advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Patient D, with dense face-processing problems consequent to a right-sided lesion in an analogous site, showed no impairment in any lip-reading task. By contrast, in normal subjects, it has been reported (a) that matching a still photograph of a lip-shape to an aftercoming speechsound was faster in the LVF/right hemisphere than the RVF/left hemisphere [3], and (b) that very slight asymmetries in favour of the right hemisphere can sometimes be found for audiovisual dubbed speech sounds [1,7]. Furthermore, two commisurotomized patients, NG and JW, do not show a clear left hemisphere advantage in the few speech-reading tasks which have been explored [1,4].…”
Section: Introductionmentioning
confidence: 89%